AN OVERVIEW OF APPLIED LINGUISTICS - Rosdiana (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2016)
The application of linguistics to the study and improvement of language teaching, language learning, language planning, communication between groups, speech therapy and the management of language handicap, systems of communications, translating and interpreting, and lexicography. The bulk of the work of applied linguists to date has related to language teaching and language learning and especially English as a foreign or second language. This study tries to review the study of language, concerns itself with all aspects of how people use language and what they must know in order to do so. As a universal characteristic of the species, language has always held a special fascination for human beings. This study try to explore the branches of linguistics are concerned with how languages are structured, how languages are used, and how they are spoken.